Intraspecies competition among Salmonella enterica isolates in the lettuce leaf apoplast - Jacob, Cristián; Student, Joseph; Bridges, David F.; Chu, Weiping; Porwollik, Steffen; McClelland, Michael; Melotto, Maeli (Frontiers in Plant Science, 2024)
Multiple Salmonella enterica serovars and strains have been reported to be able to persist inside the foliar tissue of lettuce (Lactuca sativa L.), potentially resisting washing steps and reaching the consumer. Intraspecies variation of the bacterial pathogen and of the plant host can both significantly affect the outcome of foliar colonization. However, current understanding of the mechanisms underlying this phenomenon is still very limited. In this study, we evaluated the foliar fitness of 14 genetically barcoded S. enterica isolates from 10 different serovars, collected from plant and animal sources. The S. enterica isolates were vacuum-infiltrated individually or in pools into the leaves of three- to four-week-old lettuce plants. To estimate the survival capacity of individual isolates, we enumerated the bacterial populations at 0- and 10- days post-inoculation (DPI) and calculated their net growth. The competition of isolates in the lettuce apoplast was assessed through the determination of the relative abundance change of barcode counts of each isolate within pools during the 10 DPI experimental period. Isolates exhibiting varying apoplast fitness phenotypes were used to evaluate their capacity to grow in metabolites extracted from the lettuce apoplast and to elicit the reactive oxygen species burst immune response. Our study revealed that strains of S. enterica can substantially differ in their ability to survive and compete in a co-inhabited lettuce leaf apoplast. The differential foliar fitness observed among these S. enterica isolates might be explained, in part, by their ability to utilize nutrients available in the apoplast and to evade plant immune responses in this niche.